2017
DOI: 10.1186/s12896-017-0398-6
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities and chemical compositions of slime tracks and crude exopolysaccharides isolated from plasmodia of Physarum polycephalum and Physarella oblonga

Abstract: BackgroundThe myxomycetes derive their common name (slime molds) from the multinucleate trophic stage (plasmodium) in the life cycle, which typically produces a noticeable amount of slimy materials, some of which is normally left behind as a “slime track” as the plasmodium migrates over the surface of a particular substrate. The study reported herein apparently represents the first attempt to investigate the chemical composition and biological activities of slime tracks and the exopolysaccharides (EPS) which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
0
16
0
2
Order By: Relevance
“…In previous antioxidant studies, it was reported that crude extracts isolated from the plasmodia of Physarum polycephalum and Physarella oblonga exhibited DPPH activities. 22 In the present study, it was determined that P. album had antioxidant capacity. Mushroom species were also used in previous TAS, TOS and OSI studies.…”
Section: Tas Tos and Osimentioning
confidence: 73%
See 1 more Smart Citation
“…In previous antioxidant studies, it was reported that crude extracts isolated from the plasmodia of Physarum polycephalum and Physarella oblonga exhibited DPPH activities. 22 In the present study, it was determined that P. album had antioxidant capacity. Mushroom species were also used in previous TAS, TOS and OSI studies.…”
Section: Tas Tos and Osimentioning
confidence: 73%
“…Antimicrobial studies conducted on myxomycetes reported that Physarum polycephalum and Physarella oblonga had antimicrobial effects on S. aureus, Salmonella typhi and C. albicans. 22 Furthermore, it was reported that different concentrations of the ethanol and chloroform extracts of Lycogala epidendrum exhibited antimicrobial activities against 19 different microorganisms. 23 In the present study, EtOH, MeOH and DCM extracts of P. album were used, and it was determined that it had antimicrobial activities on S. aureus, S. aureus MRSA, E. faecalis, E. coli, P. aeruginosa, K. pneumoniae, A. baumannii, C. albicans, C. krusei and C. glabrata.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Slime molds (myxomycetes) are a group of unique protozoans for which the common name (i.e., “slime molds”) most often used is based on the fact that they excrete noticeable amounts of slimy materials in both liquid and solid culture [ 14 ]. Among the myxomycetes, those members of the order Physarales (e.g., P. polycephalum ) often form large plasmodia and are relatively easy to culture on synthetic media.…”
Section: Introductionmentioning
confidence: 99%
“…Among the myxomycetes, those members of the order Physarales (e.g., P. polycephalum ) often form large plasmodia and are relatively easy to culture on synthetic media. When cultured in liquid media, microplasmodia are formed instead of plasmodia [ 14 ]. Plasmodia and microplasmodia possess several important characteristics, including having no cell walls, rapid growth, and probably sharing the same set of metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Os esporocarpos dos mixomicetos e os resíduos do plasmódio podem servir como locais de postura e fontes de alimento para coleópteros e outros insetos (HUYNH et al, 2017). Diferentes grupos de fungos atuam como saprófitos ou parasitas dos mixomicetos, na maioria das vezes inviabilizando a dispersão dos esporos (MUELLER; BILLS; FOSTER, 2004).…”
Section: Introductionunclassified